Cellular mechanisms of action of resveratrol in regulation of aqueous humour dynamics / Norhafiza Razali - Razali, Norhafiza (Institute of Graduate Studies, UiTM, 2017)
Glaucoma, a common cause of optic neuropathy, is associated with elevated intraocular pressure (IOP) and is the leading cause of irreversible visual disability. Steroid-induced glaucoma, a common type of secondary glaucoma, is also associated with elevated IOP (steroid-induced ocular hypertension (SIOH)). SIOH and glaucoma are currently treated with antiglaucoma agents, which often have suboptimal efficacy and are associated with adverse effects. The objective of this study was to determine if topical application of transresveratrol reduces IOP in rats with SIOH and to investigate its mechanisms of action. This study was divided into in vivo and in vitro studies. In the in vivo study, we evaluated the oculohypotensive effects of topical transresveratrol in normal and SIOH rats and investigated the role of adenosine receptors (ARs) and transforming growth factor-β (TGF-β) signalling in the IOP lowering effect of trans-resveratrol. Involvement of AR was studied by observing the IOP changes in response to trans-resveratrol after pretreating SIOH animals with AR subtype-specific antagonists. The study also investigated phospholipase C (PLC) activation, extracellular regulated kinase 1/2 (ERK1/2) phosphorylation and increased matrix metalloproteinases (MMPs) secretion in the aqueous humour (AH) as mechanism of resveratrolinduced oculohypotension in SIOH rats. In vitro studies evaluated the effect of trans-resveratrol on cellular signalling pathways of ARs and TGF-β in primary human trabecular meshwork cells (HTMCs)…